Association of medication adherence with clinical outcomes and quality of life in type 2 diabetes mellitus patients: a cross-sectional study - Fandinata, Selly Septi; Putra, Deddy Aryanda; Lubada, Eziah Ika; Sari, Silfiana Nisa Permata; Devientasari, Chinthia; Ernawati, Iin; Suryandari, Mercyska; Berliana, Dini (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Type 2 diabetes mellitus is a chronic metabolic disorder characterized by elevated blood glucose levels. Patient adherence to medication is a critical factor in effective management, as it can reduce morbidity and mortality while improving health-related quality of life (HRQoL). Digital interventions, such as smartphone-based medication reminder applications, represent a promising strategy to enhance adherence. Objective: This study aimed to examine the relationship between medication adherence and clinical outcomes, specifically fasting blood glucose levels and HRQoL, among patients with type 2 diabetes in primary health care settings. Methods: A cross-sectional pre–post test design was employed involving 96 respondents, divided equally into control and intervention groups, selected through convenience sampling. Primary data were collected using the MARS-10 adherence questionnaire and the DQOL Brief Clinical Inventory, while secondary data were obtained from pre– and post–fasting blood glucose measurements. Results: Results showed no significant relationship between medication adherence and fasting blood glucose levels (p > 0.05), nor between adherence and HRQoL (p > 0.05), even with the implementation of the Drug Reminder App intervention. Conclusion: These findings highlight the need for additional interventions or further innovations in digital adherence support to improve clinical and quality-of-life outcomes in type 2 diabetes management.